The hacker's guide to OS X exploiting OS X from the root up - Bathurst, Robert (Syngress, 2013)
Written by two experienced penetration testers the material presented discusses the basics of the OS X environment and its vulnerabilities. Including but limited to; application porting, virtualization utilization and offensive tactics at the kernel, OS and wireless level. This book provides a comprehensive in-depth guide to exploiting and compromising the OS X platform while offering the necessary defense and countermeasure techniques that can be used to stop hackers As a resource to the reader, the companion website will provide links from the authors, commentary and updates. Provides relevant information including some of the latest OS X threats. Easily accessible to those without any prior OS X experience. Useful tips and strategies for exploiting and compromising OS X systems. Includes discussion of defensive and countermeasure applications and how to use them. Covers mobile IOS vulnerabilities